Convergence of the solutions for the equation x(iv)+ax ⃛+bx¨+g(x˙)+h(x)=p(t,x,x˙,x¨,x ⃛) - Anthony Uyi Afuwape (International Journal of Mathematics and Mathematical Sciences)
This paper is concerned with differential equations of the formx(iv)+ax ⃛+bx¨+g(x˙)+h(x)=p(t,x,x˙,x¨,x ⃛)where a, b are positive constants and the functions g, h and p are continuous in their respective arguments, with the function h not necessarily differentiable. By introducing a Lyapunov function, as well as restricting the incrementary ratio η−1{h(ζ+η)−h(ζ)}, (η≠0), of h to a closed sub-interval of the Routh-Hurwitz interval, we prove the convergence of solutions for this equation. This generalizes earlier results.